Wisitrassameewong, K., Nuytinck, J., Le, H.T., De Crop, E., Hampe, F., Hyde, K.D. & Verbeken, A. (2015) Lactarius subgenus Russularia (Russulaceae) in South-East Asia: 3. new diversity in Thailand and Vietnam. Phytotaxa 207 (3): 215–241. - Wisitrassameewong, K.; Nuytinck, J.; Le, H.t; de Crop, E; Hampe, F; Hyde, K.d; Verbeken, A (Phytotaxa, 2015)
Three corrections been made.